STATE OF DRINKING WATER SUPPLY TO THE POPULATION OF MBAD OF THE REPUBLIC OF TAJIKISTAN - N.B. BAKHTIYOROVA; K.N. DABUROV (Avicenna Tajik State Medical University, 2019)
Objective: Study of the state of drinking water supply to the population of MBAD of the Republic of Tajikistan Methods: Materials of surveys of 16 water structures and laboratory researches of 108 samples of drinking water on chemical and microbiological indices for 2016-2017 are used. Results: The urban population of the region is 18.7% provided with piped drinking water, the rest of the population of the region (81.3%) uses water from various sources of hazardous epidemiological relations (rivers, springs, aryks, houses, wells, etc.). To address water-related problems, over the past seven years (2010-2017), a number of projects on the provision of drinking water to the population were adopted at the regional and district levels by Khukumat. Conclusion: In the MBAD, the provision of safe drinking water to the population is still low, especially in rural localities. Positive changes in the provision of drinking water to the population will create satisfactory social and sanitary, epidemiological conditions and improve the quality of life population.